Papillary Carcinoma of the Third Part of the Duodenum: A Case Report and Review of the Literature (Journal of Chittagong Medical College Teachers' Association, 2010)
Due to errors in this paper, a corrected version is reprinted in Vol.20(2) 2009 p.56-59.Key words: distal duodenal tumour; intractable vomiting; resection DOI: 10.3329/jcmcta.v20i1.4942 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):68-71